1993
DOI: 10.1021/bi00069a022
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the internalization of phosphodiester oligodeoxynucleotides in HL60 cells

Abstract: We have examined the cellular association and internalization of phosphodiester (PO) oligodeoxynucleotides (oligos) with HL60 cells. At 4 degrees C, a 15-mer PO homopolymer of thymidine (FOdT15) exhibits apparent saturation binding (Km = 22 +/- 1 nM) that is competitive with the binding of phosphorothioate (PS) oligos. The value of Kc for SdC28, a PS 28-mer homopolymer of cytidine, is 5 +/- 2 nM. SdC28 was used to strip cell surface fluorescence: Internalized fluorescence accumulated in a (concentration)(time)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(68 citation statements)
references
References 24 publications
3
63
0
1
Order By: Relevance
“…The reduction of the toxic effect of GT 3 since control CT 3 , GC 3 , AT 3 and GA 3 containing the same pyrimidine/purine values or the same number of T or G bases in PMA-treated cells is not due to a decrease of oligonucleotide uptake upon phorbol ester administration; in fact, administration with respect to toxic GT 3 do not result in significantly altered cellular growth. In addition, we verified that the administration of PMA can increase the oligonucleotide uptake during the first 24 h [8] and we found that 24 h after the administration of PMA of monophosphate or triphosphate-nucleotides at the same concentrations as those of toxic GT n do not alter the cellular growth or IL-2, the GT3 uptake does not differ from that of an untreated control culture (data not shown). In agreement with the decrease of the human cancer cell lines (data not shown).…”
Section: Cellular Toxicity Exerted By Gtn Might Involve the Binding Tsupporting
confidence: 58%
“…The reduction of the toxic effect of GT 3 since control CT 3 , GC 3 , AT 3 and GA 3 containing the same pyrimidine/purine values or the same number of T or G bases in PMA-treated cells is not due to a decrease of oligonucleotide uptake upon phorbol ester administration; in fact, administration with respect to toxic GT 3 do not result in significantly altered cellular growth. In addition, we verified that the administration of PMA can increase the oligonucleotide uptake during the first 24 h [8] and we found that 24 h after the administration of PMA of monophosphate or triphosphate-nucleotides at the same concentrations as those of toxic GT n do not alter the cellular growth or IL-2, the GT3 uptake does not differ from that of an untreated control culture (data not shown). In agreement with the decrease of the human cancer cell lines (data not shown).…”
Section: Cellular Toxicity Exerted By Gtn Might Involve the Binding Tsupporting
confidence: 58%
“…Depending on the ODN extracellular concentration, they may enter the cells either by specific absorptive endocytosis or by pinocytosis [29][30][31]. Although natural phosphodiester ODNs undergo a rapid extra-intracellular degradation [32,33], they can partially persist in the cell and rapidly reach the nucleus [12,34,35].…”
Section: Resultsmentioning
confidence: 99%
“…32 Blocking the binding of these proteins to their natural receptor is a possible mechanism for our results. However, this is questionable since the affinity was shown to be length-dependent, rather than sequence-dependent, 33 and the observed antirestenotic effect was sequence-dependent (the SC sequence had no effect).…”
Section: Figure 6 Inhibition Of Pdgf-bb Stimulated Rat Smc Proliferatmentioning
confidence: 98%